Efficacy of Metribuzin Doses on Physiological, Growth, and Yield Characteristics of Wheat and Its Associated Weeds - Javaid, Muhammad Mansoor; Mahmood, Athar; Bhatti, Muhammad Izhar Naeem; Waheed, Hasnain; Attia, Kotb; Aziz, Ahsan; Nadeem, Muhammad Ather; Khan, Naeem; Al-Doss, Abdullah A.; Fiaz, Sajid; Wang, Xiukang (Frontiers in Plant Science, 2022)
In the present scenario of increasing concerns of food safety, environmental integrity and weed resistance, it is imperative to develop approaches that could enhance herbicide efficacy at lower dose. Appropriate dose and suitable combination of metribuzin with adjuvants might be maximized wheat production by suppressing wheat weeds. This study was performed with the aim to assess the effectiveness of various doses of metribuzin alone or with adjuvants (Bio-power and Ad-500) on wheat growth, yield and its allied weeds. Metribuzin at 175, 140 and 105 g a.i/ha each separate and in combination with adjuvants (Bio-power or Ad-500 ) at 400 mL ha-1 were sprayed. Weedy check was also included as control treatment. The photosynthetic activity, number of weeds, weeds biomass were significantly affected by all herbicides along with adjuvant. However, maximum inhibition of weeds was observed where metribuzin at 175 g a.i ha-1+Bio-power at 400 mL/ha were sprayed. Metribuzin sprayed at 175 g a.i ha-1 with or without Bio-power recoded maximum 1000-grian weight, biological and grain yield. Conclusively, metribuzin sprayed at 175 g a.i ha-1+Bio-power at 400 at mL-1ha have potential to improve wheat yield by inhibiting weed growth.